PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT MATAHARI DEPARTMENT STORE TBK CBD CILEDUG - Widia Nurani, Gina; Duddy Dinantara, Mohamad (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
determine the influence of the work motivation on employee performance, to determine the influence of work discipline and the work motivastion simultaneously on employee performance. The method used is associative quantitative. The sampling technique used was a census using a sample of 60 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, multiple linear regression correlation analysis. Data analysis uses validity tests, reliability tests, classical assumption tests, correlation analysis, multiple linear regression analysis. The results of this research are a correlation coefficient of 0.833, meaning that the two variables have a strong level of influence or relationship on the employee performance variable (Y) with a coefficient of determination of 69.3%. With the results of this research, work discipline has a sig of 0.000 < 0.05, so Ho is rejected and Ha is accepted, which means that work di has a significant and influential effect on employee performance. The work motivation has a sig of 0.000 < 0.05, so s rejected and Ha is accepted, which means the work motivation has effect and is significant on employee performance. Fcount 64.638 >3.16 and sig 0.000 < 0.05 then Ho is rejected and Ha is accepted then Ho is rejected Ha is accepted which means that work discipline and motivation have a simultaneous and significant effect on employee performance. An effective work discipline and a conducive work motivation will be able to improve employee performance Keywords: work discipline, work motivation, and Employee Performance